How do Teachers Teach Mathematics and Science in English? - Suharyadi Suharyadi (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2013)
Teaching mathematics and science in English has been a hot topic in the academic amospheres such as at schools, universities, and research centers. Teaching mathematics and science in English, in this context, is the teachers’ use of English as amedium of instruction in delivering the content subjects: mathematics, biology, chemsitry and physics. In particular, teachers use English in order to open classes/greet students, review previous topics, inform topic(s) to be learned, ask questions, answer questions, explain concepts, give directions, and do parting, all of which are embodied in words, phrases and sentences. However, these classroom activities might not be easily accomplished as teachers’ English skills are not well prepared. Since they are not the English specialists, they likely use strategies in their classroom communication with their students. They use strategies in order to make their messages comprehensible to students. Their “language” (words, expressions, phrases, and sentences) should be simple and understandable so that students can figure out what is presented and taught easily. This paper is intended to report a case study on (1) types of communication strategies employed by the teachers in teaching mathematics, chemistry, and biology in English; and (2) why they use such kinds of communication strategies in teaching mathematics, chemistry, and biology in English. The data obtained from observations (through videotaping), interviews, and questionnaires indicate that the teachers deploy several communication strategies with different reasons in teaching